The role of Universal Grammar and crosslinguistic influence in the interpretation of recursive set-subset adjectives in adult Romanian L1-English L2 bilinguals - Bleotu, Adina Camelia; Foucault, Deborah; Roeper, Tom; Lakshmanan, Usha (Frontiers in Human Neuroscience, 2025)
Our research contributes to debates about the role of Universal Grammar constraints and crosslinguistic influence in sequential bilingual acquisition and use. We investigate experimentally how adult Romanian L1-English L2 bilinguals interpret sequential adjectival modifiers of a noun in recursive set-subset contexts in both languages (e.g., flori mici roşii, lit. ‘flowers small red’ in Romanian L1, red small flowers in English L2, meaning ‘the subset of red flowers among the set of small flowers’, and not the coordinative ‘the red and small flowers’). We ask whether the Recursive Set-Subset Ordering (RSSO) Constraint is observed in both Romanian L1 and proficient English L2 speakers, such that the adjective closer to the head noun indicates the set and the adjective further away indicates the subset. Our study employs a story-based, forced choice comprehension task to test RSSO against Adjective Ordering Restrictions (AORs), as two competing possible sources for adjective ordering and interpretation. While AOR captures ordering preferences of adjectives naming conceptual properties (e.g., ASize AColor N in English, N AColor ASize in Romanian), RSSO posits a structure-dependent principle in terms of sets and subsets (e.g., ASubset ASet N in English, N ASet ASubset in Romanian). We find that bilinguals adhere to the RSSO in both languages even in contexts where AOR and RSSO are in conflict. This finding supports RSSO’s status as a UG syntactic-semantic constraint. Interestingly, for a few participants, we also found evidence for crosslinguistic influence stemming from language-specific differences in branching directionality, linear order, and AORs.